Suspected de novo Hepatitis B in a Patient Receiving Anti-Tumor Necrosis Factor Alpha Therapy for the Treatment of Crohn's Disease - Ishida, Tetsuya (S. Karger AG, 2014)
We report a 45-year-old female patient who developed acute hepatic disorder during anti-tumor necrosis factor α therapy for the treatment of Crohn's disease (CD). She was diagnosed as colonic CD and placed on infliximab (IFX). She was negative for hepatitis B surface antigen at the initiation of IFX therapy, but developed acute hepatitis after the 30th administration of IFX 4 years and 1 month after the first administration. She was suspected to have had occult hepatitis B virus infection before IFX therapy, and de novo hepatitis B was considered the most likely diagnosis. Hepatitis subsided after discontinuation of anti-tumor necrosis factor α therapy and initiation of treatment with entecavir. She started to receive adalimumab to prevent relapse of CD. She has continued maintenance therapy with entecavir and adalimumab and has since been asymptomatic. As de novo hepatitis B may be fatal, virological testing for hepatitis B is essential for patients who are being considered for treatment that may weaken the immune system.